Antitesis Pola Perkataan Karakter-Konsekuensi pada Amsal 28:20 sebagai Kualitas Hidup Orang Percaya dalam Mengatasi Judi Online - Aska Pattinaja; Zefanya Puryana; Farel Yosua Sualang (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
Proverbs 28:20 is one of the passages that emphasizes the antithesis between a trustworthy person and a person who wants to get rich quickly based on the character-consequence pattern of speech (the character-consequence pattern is a structural pattern in the book of Proverbs that takes into account character actions and the consequences that will be received). The tendency of people today is to live materialistically which encourages someone to get rich quickly through shortcuts, namely online gambling, thus damaging the quality of life of believers. The purpose of this study is to provide a reference for every believer to have to build the right quality of life so as not to fall into the trap of online gambling. By using a qualitative method with sub-intrepetative design, especially wisdom literature hermeneutics, to examine the analysis of the character-consequence pattern of Proverbs 28:20, this article finds three interrelated character-forming factors, namely: first, faithfulness, as the main character-forming factor because it relates to integrity; second, the patience factor, which is an important factor that prevents making wrong and hasty decisions; third, the obedience factor, which guarantees the right decision in the face of various challenges to persist through the process to the end so that believers avoid punishment. This study serves as an input and warning for everyone to have good character in accordance with Biblical values so as to become a trustworthy person.